TEACHING FOREIGN LANGUAGES TO YOUNG STUDENTS - Kabilova Kamola; Nazarova Marjona Oktam qizi (Ustozlar uchun, 2025)
Annotation: This article highlights the relevance of the process of teaching a foreign language to young students, the effectiveness of teaching methods, and the importance of visual and interactive tools. Today, in the context of globalization, the need to teach foreign languages ​​from an early age is increasing. The study analyzes the role of psychological and pedagogical approaches, game methods, and multimedia technologies appropriate to the age of children. The motivational role of the teacher, family environment, and social factors are also indicated as decisive factors in the effective acquisition of a foreign language.